Economic analysis of advance tax rulings - Markus Diller; Pia Vollert (Arbeitskreis Quantitative Steuerlehre (arqus), 2011)
This paper aims to analyze the impact of applying for an advance tax ruling and of examining complex tax issues with the help of an external consultant, on the investor's decision to invest when the environment is uncertain. Using decision theory, we first determine the maximum fee an investor is willing to pay for such a ruling or consultation in order to firm up the investment decision. We expand our analysis by assisting the potential investor in deciding on the maximum fee he is willing to pay for such a service when the fee for an advance tax ruling is set by law.
Keywords: H25; K34; 330; Advance Tax Rulings; Decision Theory